2018
DOI: 10.1111/ajt.14566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of match-run frequencies on the number of transplants and waiting times in kidney exchange

Abstract: Numerous kidney exchange (kidney paired donation [KPD]) registries in the United States have gradually shifted to high-frequency match-runs, raising the question of whether this harms the number of transplants. We conducted simulations using clinical data from 2 KPD registries-the Alliance for Paired Donation, which runs multihospital exchanges, and Methodist San Antonio, which runs single-center exchanges-to study how the frequency of match-runs impacts the number of transplants and the average waiting times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…20 There is some concern that this behavior is inefficient (and arguably a result of competition). However, numerical simulations by Ashlagi et al (2017) suggest that in steady-state there is essentially no harm from frequent matching (though having multiple small platforms does harm efficiency). Moreover, MSA is not facing any competition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 There is some concern that this behavior is inefficient (and arguably a result of competition). However, numerical simulations by Ashlagi et al (2017) suggest that in steady-state there is essentially no harm from frequent matching (though having multiple small platforms does harm efficiency). Moreover, MSA is not facing any competition.…”
Section: Resultsmentioning
confidence: 99%
“…11 Akbarpour et al (2014) consider a homogeneous model with departures and finds that the optimality gap of the policy that matches without waiting remains constant as the match probability decreases. Moreover, using data-driven simulations, Ashlagi et al (2017) study the impact of match-run frequency, and show that among polices that match periodically (e.g., every week or every day), high matching frequencies perform best. 12 This paper builds on these findings, and only analyzes myopic policies that search for a match upon arrival of a new agent.…”
Section: Related Workmentioning
confidence: 99%
“…Despite this change APD-KPD patients had only 3% of transplants with delayed graft function (DGF), which was similar to 4% in OPTN-KPD and to 4.5% in OPTN-LD ( Figure S1B). Additional review of donor's age in APD-KPD showed that despite 7-h CIT grafts from 50to 64-year-old donors had similar 3-year graft survival as from young [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] year-old donors, which was confirmed by a parallel analysis of APD-LD, OPTN-KPD and OPTN-LD ( Figure S2A-E). Thus, we found no disadvantage in the use of older donors for the KPD program.…”
Section: Apd-kpd Performancementioning
confidence: 70%
“…In contrast, one failed transplant in a cycle scrapped all planned transplants. Even with an average CIT of 7-h 50-64 year old donors produced good quality transplants comparable to [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] year old donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation